HUBUNGAN ANTARA PEMANTAUAN INTAKE OUTPUT CAIRAN PENDERITA CKD DENGAN TERJADINYA OVERLOAD CAIRAN: - AJENG RUVITA DEWI (LPPMK STIKES Widyagama Husada, 2022)
Abstract Monitoring fluid intake and output in patients with CKD is the main action to reduce the occurrence of fluid overload in patients with CKD. Fluid overload can cause shortness of breath, edema, and acites. Lack of attention to fluid intake and output will lead to more serious health problems. This study aims to determine the relationship between monitoring of CKD fluid intake output and the occurrence of fluid overload at RSU Karsa Husada Batu. The research design used was Correlative Study. Retrieval of data using Cross Sectional. The sampling method used was Purposive Sampling. The sample in this study amounted to 22 people. The intake output monitoring variable was assessed using the fluid intake output chart questionnaire, while the fluid overload variable was the head to toe observation sheet. The result of the Spearman Rank Correlation test shows a p value of 0.001 where the p value is smaller than alpha 0.05 (p value (0.001) <alpha (0.05), which means that there is a significant relationship between monitoring the fluid output intake of patients with CKD and the occurrence of fluid overload in RSU Karsa Husada Batu. The correlation coefficient of 0.661 is a number that is positive. So the relationship between Monitoring Intake of Fluid Output for CKD Patients with the Occurrence of Fluid Overload is unidirectional, thus it means that the better monitoring of fluid output intake for CKD sufferers, the risk of overload Also decreasing The effectiveness of limiting the amount of fluids in CRF patients depends on the patient's knowledge of the amount of fluids that can be drunk and efforts to create restrictions on fluid intake through monitoring the intake of fluid output per day . This is very necessary to be applied consistently in patients with CKD. Keyword : monitoring of fluid intake, output, overload.